Toronto the Good? Negotiating Race in the Diverse City - Almeida, Shana (University of Toronto Press, 2022)
Armed with the motto "Diversity Our Strength," the City of Toronto has garnered a world-class reputation for challenging racism, largely because of how it is seen to value and include racialized groups through its diversity policies and practices. Toronto the Good? unsettles popular depictions of both diversity and the City of Toronto by attending to what diversity does in and for the City in the context of historical relations of race. Toronto the Good? brings together Shana Almeida's critical insights as a former political staff member along with her years of in-depth research on diversity in the City of Toronto to offer a compelling case to rethink how we understand diversity and racial inclusion in the City of Toronto and beyond. Initiated in a local context, Toronto the Good? critically contributes to global discussions on diversity, race, democracy, political participation, and power.